Unleashing the Power of Words: Group Discussion for EFL Students' Speaking Skills - Artayani, Kadek Dita Dwi (English Teaching and Linguistics Journal (ETLiJ), 2024)
Speaking English is one of the skills that EFL students have to mastering. The ability of speaking can be implemented by using group discussion where students express their ideas freely which helps to encourage its speaking skills.  Several studies have been examined the factors and problems that caused students in speaking skill, but the explore of implementation and analyzing speaking skills through group discussion are still limited. This research aims to explain how an English teacher at school applied a group discussion for students’ speaking skills related to the problem they faced during study. This research conducted by following stages of library research and was analyze qualitatively. The data was collected from journal that accredited national and international. The findings shows that group discussion as a part of innovative method significantly enhance students’ engagement and learning outcomes in speaking skills. The important of implementing group discussion help to increase students speaking skill. Most student faced the same problem in speaking whether in linguistic and non-linguistics problems. Lack of pronunciation, vocabulary, less confidence and the used of mother language is the most main problem faced by students in speaking EFL. Thus, future researcher may explore more the strategies and its implications in teaching English as a Foreign Language especially for adult learners' speaking skills.